Factors contributing to glass ceiling in private organizations in Menara MSC Cyberport / Nurul Fatehah Mohd Salim - Mohd Salim, Nurul Fatehah (Faculty of Business and Management, 2018)
The intention of this research is to examine the elements that cause glass ceiling in the private organizations in Menara MSC Cyberport. The chapters that will be discussed are research background, problem statements, research objectives, research questions, hypothesis and significance of the research.